2005
DOI: 10.1080/0958519042000339543
|View full text |Cite
|
Sign up to set email alerts
|

The impact of business ownership change on employee relations: buy-outs in the UK and The Netherlands

Abstract: A buy-out is a fundamental change in the structure of ownership that may affect the way employee relations develop within an organisation. Little is known about the impact of buyouts upon employee relations. This paper aims to address this gap. We focus on two main questions. First, what are the effects of a buy-out on employee relations in an organisation? Second, does the national institutional context affect the impact of buy-outs on employee relations? The paper reports changes to employee relations in buy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 51 publications
(54 reference statements)
2
46
1
Order By: Relevance
“…To fill this gap, some U.K. and European authors have amassed an extremely rich dataset to assess the effects of management buyouts on employee "empowerment" and other aspects of the work environment. Bruining et al (2005) report that MBOs result in an improvement in human resource management practices in the U.K. and the Netherlands. Specifically, they found that there were higher levels of employment, employee empowerment, and wages.…”
Section: Real Effects Of Buyoutsmentioning
confidence: 98%
“…To fill this gap, some U.K. and European authors have amassed an extremely rich dataset to assess the effects of management buyouts on employee "empowerment" and other aspects of the work environment. Bruining et al (2005) report that MBOs result in an improvement in human resource management practices in the U.K. and the Netherlands. Specifically, they found that there were higher levels of employment, employee empowerment, and wages.…”
Section: Real Effects Of Buyoutsmentioning
confidence: 98%
“…Unless private equity firms are part of this dramatic change, they may be expected to work with unions in European countries with stronger codetermination legislation, whereas they may operate relatively free of union constraints in countries with more permissive worker representation legislation. However, research on buyouts in both the UK and The Netherlands, the latter having a higher degree of employment protection, reported the positive effects of buyouts on employment practices are surprisingly greater in the less regulated UK context than in The Netherlands (Bruining et al, 2005). Watt (2008: 562) suggests private equity is probably "'unideological'', if unsentimental, in its approach to issues such as collective bargaining and worker participation', unless urgent restructuring is required and opposed by unions.…”
Section: Private Equity Buyouts and Industrial Relationsmentioning
confidence: 99%
“…In extremis, this may involve 'grand-scale union busting' as part of a general management antagonism towards unions (ITUC, 2007). To support these claims, the ITUC (2007) points to evidence from the Centre for Management Buy-out Research (CMBOR) of slight declines in union recognition in UK and Dutch buyouts (Bruining et al, 2005), managers in buyouts with negative views towards unions (Bacon et al, 2004), and after reviewing this evidence the Work Foundation concludes 'the combination of a pre-existing hostility to trade unions and the fall in recognition of a union after a buyout would imply that derecognition was . .…”
Section: Private Equity Buyouts and Industrial Relationsmentioning
confidence: 99%
“…One is cost reduction, with the Automobile Association (AA) in the UK being a celebrated example where more than 3,000 jobs -nearly 30% of the workforce -were axed. The alternative is investment (Bruining et al, 2005). Alliance Boots was an example of an MBO and, it transpired, the new private equity owners were to take an investment approach.…”
Section: The Virtuous Business Organizationmentioning
confidence: 99%